Simultaneous preconcentration of both polar and non-polar Q-markers of flavonoids in traditional Chinese medicine by reverse micellar floating solidification liquid-phase microextraction. Issue 13 (9th August 2021) - Xie, Zhong-shui; Xing, Rong-rong; Chen, Xuan; Hu, Shuang; Bai, Xiao-hong
Abstract: A reverse micellar floating solidification liquid-phase microextraction was proposed for simultaneous preconcentration and determination of both polar (scutellarin, baicalin) and non-polar (scutellarein, luteolin, apigenin, wogonin) quality-markers of flavonoids in traditional Chinese medicine coupled with high performance liquid chromatography-ultraviolet detection. In this work, the reverse micelle of Aliquat 336/dodecanol as the extractant was used to enrich target analytes. The synthesis of the reverse micellar extractant was investigated, and its microstructure was characterized by fluorescence microscope and transmission electron microscope. The variables affecting the experimental procedure, including reverse micelle volume, sample phase pH, salt amount, extraction temperature, extraction time and stirring rate were investigated and optimized. Under the optimum conditions, enrichment factors between 155 and 329 for the target analytes, satisfactory linear ranges ( r  ≥ 0.9983), low detection limits (0.05–0.25 ng mL −1 ), acceptable precisions (relative standard deviations of 0.2–8.9%) and accuracies (recoveries of 87.2–108.5%) were obtained. The extraction mechanism based on reverse micelle was explored and elucidated. The characteristics of the proposed method were summarized by comparison with others. The developed approach was successfully applied for the extraction and concentration of six quality-markers of flavonoids with different polarities from a traditional Chinese medicinal herb of Scutellariae Barbatae Herba. Graphical Abstract: UF0001